A Case of Acute Vestibular Neuritis Visualized by Three-Dimensional FLAIR-VISTA Magnetic Resonance Imaging. (April 2014) - Park, Kang Min; Shin, Kyong Jin; Ha, Sam Yeol; Park, Jin Se; Kim, Sung Eun
Abstract A 72-year-old man presented with vertigo and unsteady gait. The three-dimensional fluid-attenuated inversion recovery–volume isotopic turbo spin echo acquisition (3D-FLAIR-VISTA) magnetic resonance imaging (MRI) showed high signal intensity in the cisternal segment of the right vestibular nerve. The video-based oculography with caloric test revealed spontaneous left-beating nystagmus and canal paresis in the right ear. This case suggests that 3D-FLAIR-VISTA images are useful for the visualisation of acute vestibular neuritis.